Landscaping for heat rejection design of natural convection cooling device / Hambali Hussein, Hairiazlan Kasbon and Jan Mohammad Zain Ibrahim - Hussein, Hambali; Kasbon, Hairiazlan; Ibrahim, Jan Mohammad Zain (1994)
A study of natural convection flow and heat and mass transfer mechanism between a flowing hot water and the moist air is the subject of this project. The main purpose is to provide an analysis for this area, in recognition of the tremendous interest that presently exists in it and of its importance in a wide range of problems and areas. The utilisation of ambient air in the heat transfer mechanism should be maximised because the properties of the air are suitable in the process. The cost of handling the air in this analysis is zero, therefore this analysis can provide the world of engineering a cheap alternative of cooling device. Principally, this project covers heat transmission, psychrometrics, mass transfer, and landscape design. The field of heat transfer is so wide and diversified that an orderly presentation of scientific facts is essential for the analysis. Finally, these principles can be the basic guidelines in the preparation of the cooling device design. Chapter 2 builds up the necessary formulation in the analysis and chapter 5 will show an example of application.